2012
DOI: 10.5698/1535-7511-12.4s.7
|View full text |Cite
|
Sign up to set email alerts
|

The Brain, Seizures and Epilepsy Throughout Life: Understanding a Moving Target

Abstract: The Scope of the Problem The incidence of seizures and of epilepsy varies throughout life, peaking in neonates and children and increasing again after the age of 50 (1-4). In addition to the quantitative measure of the incidence of seizures, the type of seizures (and of epilepsy syndromes) varies with age: for example, febrile seizures take place in infants and children (1, 5-7), whereas the incidence of post-stroke epilepsy increases in adults compared with children (1,3,8). What is the basis of these age-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 128 publications
1
20
0
1
Order By: Relevance
“…Two previous studies have reported trends for higher rates of psychiatric diagnoses in older children and adolescents compared to younger children with epilepsy; however, as mentioned previously, age groups vary across studies. 2,18 As a process of puberty, adolescents with epilepsy may experience neuropathophysiological changes, 13 and/or psychosocial factors are more influential in adolescence (e.g. social isolation, independence with self-management, driving restrictions), rendering them more vulnerable to increased seizure activity and to mental health comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have reported trends for higher rates of psychiatric diagnoses in older children and adolescents compared to younger children with epilepsy; however, as mentioned previously, age groups vary across studies. 2,18 As a process of puberty, adolescents with epilepsy may experience neuropathophysiological changes, 13 and/or psychosocial factors are more influential in adolescence (e.g. social isolation, independence with self-management, driving restrictions), rendering them more vulnerable to increased seizure activity and to mental health comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…While these dynamic changes enable the flexibility necessary to wire the nervous system during development and to modify synapses during learning and memory, they pose a major challenge to the stability of neural function. Indeed, it is interesting to note that the period of highest susceptibility to seizures occurs during the first years of life, a period of dramatic synaptic growth and pliability in the nervous system (Holmes and Ben-Ari, 1998;Baram, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…the pathogenic effects of epilepsy or comorbid diseases. The ageing adult population with an adult‐ or geriatric‐onset epilepsy is at particular risk for this type of deterioration, taking into account that many factors converge in these late‐onset epilepsies: comorbidity (especially stroke and other (cardio)vascular disease), metabolic disturbances, increased inflammatory response to seizures and the use of polypharmacy . All these conditions, in conjunction with ageing and the associated decrease of the brain's neuronal plasticity, increase cerebral vulnerability and lead to irreversible loss of functional reserve capacity, eventually resulting in cascadic deterioration and acceleration of cognitive ageing.…”
Section: Introductionmentioning
confidence: 99%